Impact of ERP Implementation on SME’s Competitive Advantage with the Moderation Role of User Experience: Evidence from Pakistani SME Sector - Muhammad Yasir, Khan; Rossazana, Ab. Rahim; Sin, Kit Yeng (UNIMAS, 2025)
In the modern era of technological evolution, ERP systemsis becoming a widespread IT solution for numerous enterprises. ERP systems are now an essential part of enterprises belongs to public or private sector regardless of their sizes whether small, medium, or large. ERP system acts as a strategic tool for an enterprise to gain competitive advantage over competitors in different business processes and operations, along with planning, synchronizing, and optimizing key resources. ERP systems support multi-range functions in an organisation or enterprise from a single IT architecture. ERP systems allow organisations to automate their processes and have multiple components for different business functions such as product planning, sales, marketing, distributing, project management, inventory management, maintenance, shipping, e-commerce, sales support, production and payroll, supply chain management, logistics, financial and cost accounting, customer relationship management, manufacturing, scheduling, and human resource. ERP system implementation life cycle consist of three phases pre-implementation, implementation, and post implementation. ERP implementation phase play a vital role organisational competitive advantage. The purpose of this study was to find out ERP implementation impact within SME sector of Pakistan. Along with that the moderation effect of ERP user experience on antecedent of ERP implementation impact was also one of the key objectives of this study. This study collected data through online survey 256 respondents replied. Results of this study shows that ERP system quality, ERP information quality, ERP service quality, individual productivity, workgroup productivity, cost management and sales management were the key antecedent of ERP implementation impact. Results also showed the moderation effect of ERP user experience on ERP system quality and competitive advantage, ERP service quality and competitive advantage and individual productivity obtained from ERP system and competitive advantage were significant. This study was conducted to help SME sector of Pakistan in implementing ERP systems and to gain advantage from it in the implementation phase.